Adversity Intelligence’s Mediating Role Between Emotional Intelligence and Vaping Dependency - John Adolfo Narag Lojero; Jemerson Naceno Dominguez (Universitas Nusa Cendana, 2026)
Introduction In the past years, vape use prevalence has been marked among unfavorable workplaces including its repercussions, and the gap between adversity intelligence (AI) and vaping dependency (VD) was also evident. Aim This study aimed to determine if AI intervenes in emotional intelligence (EI) and VD and their relations. This study had Filipino (n= 388) employed young adults (18-40) through an online survey. Result The results showed medium EI, high VD, and below average AI, while EI and AI paths have a positive estimate= 0.7260, p< .001 and a negative estimate= -0.0282, p= 0.010 between AI and VD. The surprising positive estimate= 0.041, p< .001 of EI and VD was a contextual factor. Conclusion Abruptly, AI served as a suppressor (estimate= -0.006, p< 0.019) indicating that VD may reduce when EI noise is repealed. Thus, EI may positively influence AI, and AI may negatively affect VD. AI’s influence between EI and VD shows inconsistent mediation.